Brassicales phylogeny inferred from 72 plastid genes: A reanalysis of the phylogenetic localization of two paleopolyploid events and origin of novel chemical defenses. Issue 3 (25th March 2018) - Edger, Patrick P.; Hall, Jocelyn C.; Harkess, Alex; Tang, Michelle; Coombs, Jill; Mohammadin, Setareh; Schranz, M. Eric; Xiong, Zhiyong; Leebens‐Mack, James; Meyers, Blake C.; Sytsma, Kenneth J.; Koch, Marcus A.; et al.
Abstract : PREMISE OF THE STUDY: Previous phylogenetic studies employing molecular markers have yielded various insights into the evolutionary history across Brassicales, but many relationships between families remain poorly supported or unresolved. A recent phylotranscriptomic approach utilizing 1155 nuclear markers obtained robust estimates for relationships among 14 of 17 families. Here we report a complete family‐level phylogeny estimated using the plastid genome. METHODS: We conducted phylogenetic analyses on a concatenated data set comprising 44, 926 bp from 72 plastid genes for species distributed across all 17 families. Our analysis includes three additional families, Tovariaceae, Salvadoraceae, and Setchellanthaceae, that were omitted in the previous phylotranscriptomic study. KEY RESULTS: Our phylogenetic analyses obtained fully resolved and strongly supported estimates for all nodes across Brassicales. Importantly, these findings are congruent with the topology reported in the phylotranscriptomic study. This consistency suggests that future studies could utilize plastid genomes as markers for resolving relationships within some notoriously difficult clades across Brassicales. We used this new phylogenetic framework to verify the placement of the At‐α event near the origin of Brassicaceae, with median date estimates of 31.8 to 42.8 million years ago and restrict the At‐β event to one of two nodes with median date estimates between 85 to 92.2 million years ago. These events ultimately gave rise to novel chemical defenses and are associated with subsequent shifts in net diversification rates. CONCLUSIONS: We anticipate that these findings will aid future comparative evolutionary studies across Brassicales, including selecting candidates for whole‐genome sequencing projects.